Extratos de moringa no tratamento do caldo de cana e reflexos sobre a fermentação alcoólica - Macri, Rita de Cássia Vieira [UNESP] (2014)
During the process of ethanol production from the sugar cane juice, it is taken clarifying of the juice, with the purpose of removing all the yeast inhibitors. In this process, it is used synthetic polyelectrolytes with acrylamide bases, and those help the subsidence of these compounds. However, the acrylamide can present neurotoxic and cancer damage. Because of these, it is necessary to look for another products, like extracts of moringa, in order to replace the extracts used now a days. In this way, the purpose of the project was to evaluate the reflections of the sugar cane juice treatment, using some leaves and seeds extracts from the moringa’s tree on alcoholic fermentations. The experimental lineation was totally randomized in split plots, with four repetitions. The primary treatment was constituted by three different sedimentation auxiliaries (synthetic polyelectrolyte, leaves and seeds extracts from moringa’s tree) and a control treatment (without sedimentation auxiliaries), and also a secondary treatment including two varieties of sugar cane (RB867515 and CTC4). The culms were submitted to the processo f extraction, and the juice was clarified by simple soaking, with a lifting at the pH to 6,0. The different flocculants were added to the decanter previously from the warmed and soaked sugar cane juice. This clarified juice was standardized to 16º Brix and pH 4,5, yielding the lushness, which was inoculated with the yeast FT858. In the end of the brewing, the wine was obtained through centrifugation. In all the process (juice extraction, clarification, lushness and wine), it was possible to do all the technological and chemical analysis. It was possible to note higher amounts of sugar inside the juice extracted from sugar cane type CTC4 compared to the other type RB867515. Considering the clarification process of the juice, it was possible to check the values of sedimentation ...